Medidas de controle da circulação do livro didático para o ensino de leitura e escrita em São Paulo: atuação da commissão revisora de 1918 - Oliveira, Fernando Rodrigues de [UNESP]; Trevisan, Thabatha Aline [UNESP] (Associação Sul-Rio-Grandense de Pesquisadores em História da Educação, 2015)
In order to contribute to the understanding of the history of the teaching of reading and writing and the history of political movement of textbooks in Sao Paulo, Brazil, we present the results of the analysis of the documents produced by the Review Commission Textbook, established in 1918 by the General Board of Education of São Paulo State. This commission aimed to review which books among the already approved by previous committees, should continue as recommended for use in elementary schools in São Paulo. For this, the commission has prepared various reports, which are representative of the actions of the state government to control the circulation and use of textbooks in elementary schools in the early twentieth century.

In order to contribute to the understanding of the history of the teaching of reading and writing and the history of political movement of textbooks in Sao Paulo, Brazil, we present the results of the analysis of the documents produced by the Review Commission Textbook, established in 1918 by the General Board of Education of São Paulo State. This commission aimed to review which books among the already approved by previous committees, should continue as recommended for use in elementary schools in São Paulo. For this, the commission has prepared various reports, which are representative of the actions of the state government to control the circulation and use of textbooks in elementary schools in the early twentieth century.

Con el objetivo de contribuir a la comprensión de la historia de la enseñanza de la lectura y la escritura y la historia del movimiento de los libros de texto en São Paulo, Brasil, se presentan los resultados del análisis de los documentos producidos por la Comisión de revisión de los libros de texto, establecida en 1918 por el Consejo General de Educación de São Paulo. Esta comisión tenía como objetivo revisar cuales libros, entre los ya aprobados por los comités anteriores, deben continuar como se recomienda para su uso en las escuelas primarias de São Paulo. Con este fin, se produjeron diversos documentos, que son representativos de las acciones del gobierno estatal para el control de la circulación y el uso de los libros de texto en las escuelas primarias a principios del siglo 20.

Dans le but de contribuer par la compréhension de l´histoire de l´enseignement de la lecture et de l´écriture et par l´histoire des politiques de la circulation des manuels scolaires dans l´état de São Paulo, Brésil, on présente des résultats de l´analyse des documents produits par la Commission de révision des manuels scolaires, établi en 1918. Cette Commission qui visait à examiner les livres, parmi les déjà approuvé par les comités précédents, devraient continuer tel que recommandé pour une utilisation dans les écoles primaires de São Paulo. Ainsi, différents rapports ont été produits, ceux-ci sont représentatifs des actions du gouvernement de l´état pour le contrôle de la circulation et l´utilisation des manuels scolaires dans les écoles primaires au début du 20e siè...

Com o objetivo de contribuir para a compreensão da história do ensino de leitura e escrita e a história das políticas de circulação dos livros didáticos em São Paulo, Brasil, apresentam-se resultados da análise dos documentos produzidos pela Commissão Revisora de Livros Didáticos, instituída em 1918 pela Diretoria Geral da Instrução Pública de São Paulo. Esta comissão teve como objetivo rever quais livros, dentre os já aprovados por comissões anteriores, deveriam continuar como recomendados para uso nas escolas primárias paulistas, relativamente ao ensino de leitura e escrita. Para tanto, foram produzidos diferentes relatórios, os quais são representativos das ações do governo paulista para controle da circulação e do uso dos livros didáticos nas escolas primárias no início do século 20.
Control measures for circulation of the textbook for teaching reading and writing in São Paulo: the role of the 1918 reviewing committee
Medidas de control de movimiento de los livros de texto sobre enseñanza de la lectura y la escritura en São Paulo: el papel de la comisión de revisión, 1918
Keywords: Textbook; Teaching reading and writing; History of literacy; History of education; Livro didático; Ensino de leitura e escrita; História da alfabetização; História da educação